2017
DOI: 10.1038/nm.4421
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells migrate into and control simian immunodeficiency virus replication in lymph node follicles in African green monkeys

Abstract: Natural killer (NK) cells play an essential role in antiviral immunity, but knowledge of their function in secondary lymphoid organs is incomplete. Lymph node follicles constitute a major viral reservoir during infections with HIV-1 and simian immunodeficiency virus of macaques (SIVmac). In contrast, during nonpathogenic infection with SIV from African green monkeys (SIVagm), follicles remain generally virus free. We show that NK cells in secondary lymphoid organs from chronically SIVagm-infected African green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
165
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(177 citation statements)
references
References 58 publications
(74 reference statements)
11
165
1
Order By: Relevance
“…28,31 Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species. [32][33][34][35] We previously uncovered the phenotypic complexity and diversity of innate myeloid cells in the blood and the impact of vaccinations on the dynamics of their subset composition by mass cytometry 27 in cynomolgus macaques immunized with a recombinant MVA HIV-B.…”
Section: Nk Cells Are Innate Lymphoid Cells That Can Constitutively Kmentioning
confidence: 99%
See 1 more Smart Citation
“…28,31 Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species. [32][33][34][35] We previously uncovered the phenotypic complexity and diversity of innate myeloid cells in the blood and the impact of vaccinations on the dynamics of their subset composition by mass cytometry 27 in cynomolgus macaques immunized with a recombinant MVA HIV-B.…”
Section: Nk Cells Are Innate Lymphoid Cells That Can Constitutively Kmentioning
confidence: 99%
“…In addition, both human and macaque NK cells express NKp46, but in macaques, NKp46 may not be expressed by all NK cell subpopulations . Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species …”
Section: Introductionmentioning
confidence: 99%
“…AGM are known to preserve Th17 levels in the gut and to maintain an intact intestinal barrier despite high viraemia . The animals were infected with viral doses resulting in the same viraemia levels in both species (as shown for instance in the Figure of reference ). Gut biopsies were collected at day 65 post‐infection (p.i.).…”
Section: Resultsmentioning
confidence: 99%
“…CTLs do not normally express receptors that allow homing to the B cell follicle until late in untreated infection (Connick et al 2007). Therefore, B cell follicles are considered sanctuary sites for HIV-1 replication as they are shielded from CTL and/or NK cell-mediated cytolysis (Fukazawa et al 2015; Huot et al 2017). Indeed, CTL exclusion from the follicle appears to be the mechanism for viral replication within TfH cells in elite controller macaques.…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%
“…NK cells, the effectors likely responsible for antibody-mediated clearance mentioned earlier, have also been implicated in HIV-1 and SIV control (Alter et al 2011; Ramsuran et al 2018). Intriguingly, NK cells localize within and around lymph nodes in African green monkeys, a natural SIV host in which infection does not progress to AIDS (Huot et al 2017). Two major types of NK cells exist in humans, distinguished by their anatomical location.…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%